Nitrogen fertilization in consecutive cycles and its impact on high-density peach crops - Ferreira, Letícia Vanni; Picolotto, Luciano; Pereira, Ivan dos Santos; Schmitz, Juliano Dutra; Antunes, Luis Eduardo Corrêa (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effect of nitrogen fertilization on the mineral composition of leaves, initial growth, and yield of peach (Prunus persica) tree advanced selections grown at a high-planting density. The experiment was carried out between 2012 and 2015 in a randomized complete block design, with a combination of advanced selections of the 'Cascata 1513' and 'Cascata 1067' peach trees and of N fertilization doses (0, 30, 60, and 120 kg ha-1 N). Green weight after pruning, diameter, and increase of trunk diameter, canopy volume, plant height, branch length, number of buds per centimeter of shoot, chlorophyll index, leaf area, rust incidence, average production, number of fruit, and mass of fruit were evaluated. Genotype affects the vegetative growth and productive performance of peach trees. The application of N to dense peach orchards promotes a greater vegetative growth of the plants and increases the content of the nutrient in leaves. The initial production is affected by N fertilization. The recommendation of N fertilization made to date is insufficient for peach trees at high-density management systems of production.